Meningkatkan Kunjungan Wisatawan Ke Dago Dream Park Bandung - Karolin Angelia (LPPM and Travel Operation Department Universitas Asa Indonesia, 2022)
The purpose of this research is to ascertain the impact of tourism attraction, social media, and price perception on the decision to visit Dago Dream Park. Using the accidentals sampling method, this study was conducted on up to 80 tourists from Dago Dream Park. Multiple regression analysis was used as the analytical method. Based on the findings of the analysis, it is possible to conclude that the tourist attraction variable has a significant effect on the decision to visit by 0.207, with a contribution of 4%. The social media variable has a significant influence on the decision to visit by 0.249, with a contribution of 6%. Price perception has a significant effect on the decision to visit by 0.140, with a contribution of 2%. Thus, the tourist attraction variable, social media, and price perception variable all have a 0.824 influence on the decision to visit, with a 68 percent contribution, while the remaining 32 percent is influenced by other variables not included in this study.